1978
DOI: 10.3109/02841867809127916
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Gamma Irradiation of Basilar Artery in CAT: Preliminary Experiences

Abstract: Irradiation of the basilar artery of cats by stereotactic technique was performed with doses varying from 100 to 300 Gy in a gamma unit. Histologically, vascular lesions such as vacuolization, degeneration and desquamation of the endothelium and hyalinization and necrosis of the muscular coat predominated, whereas reparatory reactions were relatively sparse. Thrombosis was completely absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 4 publications
1
17
1
Order By: Relevance
“…Reports of the effects of radiosurgery on normal vessels include a study of GKS on cat basilar artery 10 and on rat anterior cerebral artery. 5 Findings included intimal proliferation but no vessel occlusion except in 1 rat anterior cerebral artery 20 months after treatment with 100 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of the effects of radiosurgery on normal vessels include a study of GKS on cat basilar artery 10 and on rat anterior cerebral artery. 5 Findings included intimal proliferation but no vessel occlusion except in 1 rat anterior cerebral artery 20 months after treatment with 100 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…In 1978 Nilsson et al reported their experience with irradiation of basilar artery in the cat [16] using the Gamma Knife. The animals were exposed to irradiation of 100, 200, 250 or 300 Gy, and were followed up to 7 months after irradiation.…”
Section: Gamma Irradiation In Laboratol 7 Animalsmentioning
confidence: 99%
“…22 Omary and colleagues 24 irradiated the frontoparietal cortex in rats by using the Gamma Knife at a single dose of 120 Gy. Four weeks later, MR spectroscopy and gadopentetate dimeglumine-enhanced T 1 -weighted MR imaging were performed.…”
Section: Vasculopathy After Radiosurgerymentioning
confidence: 99%